Violence Prevention Climate Scale: Translation, Adaptation, and Psychometric Assessment of the French Canadian Version - Marie-Hélène Goulet; Michèle Desmarais; Pierre Pariseau-Legault; Caroline Larue; Francelyne Jean-Baptiste; Jean-Sébastien Turcotte; Anne G. Crocker (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2021)
Introduction: Violence in psychiatric settings has negative consequences on patients, staff, and the institution alike. Efforts to prevent violence cannot currently be assessed due to a lack of suitable indicators. The Violence Prevention Climate Scale (VPC-14) is a validated tool that can be filled out by both staff and patients to assess the violence prevention climate in mental health care units. Objective: This study aimed to conduct the translation and adaptation of the VPC-14 to a French Canadian context, and to assess its psychometric properties in general and forensic psychiatric settings. Methods: This study followed a transcultural approach for validating measuring instruments. Psychometric properties were assessed in 308 patients and staff from 4 mental health and forensic hospitals in Quebec (Canada). Content validity was assessed using a bilingual participant approach. Internal validity was examined through exploratory factor analysis and internal consistency for each care setting using Cronbach's alpha coefficient analysis. Results: The Échelle modifiée du climat de prévention de la violence [Modified Violence Prevention Climate Scale] (VPC-M-FR) consists of 23 items with a 3-factor structure: 1) staff action, 2) patient action, and 3) the therapeutic environment. Cronbach's alphas ranging from 0.69 to 0.89 were obtained for the internal consistency of the scale. Discussion and conclusion: The VPC-M-FR has satisfactory psychometric properties for measuring the violence prevention climate in mental health and forensic settings. By measuring the violence prevention climate from the standpoint of patients and staff, targeted preventive measures can be implemented to improve safety for all.